Sosialisasi Wisata Halal dalam Perspektif Islam - Nur'aeni, Nur'aeni; Mintarsih, Mimin; Afifudin, Muhammad (Ma'soem University, 2023)
The purpose of this activity is to describe halal tourism in the view of an Islamic perspective to the people of Campakamulya Village. The method in this service activity is to use PAR (Participatory Action Research) which includes 3 stages, namely the beginning, preparation, implementation and evaluation stages. The results of the activities have been carried out well, the community, especially the managers of tourism villages, have gained knowledge about how to manage and implement sharia-based tourism villages so that they have more value than other tourism.